2022
DOI: 10.1007/s00392-022-02046-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of self-expanding versus balloon-expandable transcatheter heart valves in relation to native aortic annulus anatomy

Abstract: Objectives This study aimed to compare hemodynamic characteristics of different self-expanding (SE) and balloon-expandable (BE) transcatheter heart valves (THV) in relation to native aortic annulus anatomy. Background A patient centered THV selection becomes increasingly important as indications for transcatheter aortic valve replacement (TAVR) are extended towards lower risk populations. Methods Hemodynamic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…5H) resulting from simulating intervention in our model. We found that changes measured in this study are consistent with the literature of large-population studies of TAVR outcome ( 41 43 ).…”
Section: Discussionsupporting
confidence: 90%
“…5H) resulting from simulating intervention in our model. We found that changes measured in this study are consistent with the literature of large-population studies of TAVR outcome ( 41 43 ).…”
Section: Discussionsupporting
confidence: 90%
“…Of these, 751 were excluded because they were not pertinent to the design of the meta-analysis or did not meet the explicit inclusion criteria. Eleven observational studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] (among them seven multi-center registries), including N = 12,363 patients, were eventually included in the analysis. Potential sources of study bias were analyzed with the use of the components recommended by the ROBINS-I tool, and the results are shown in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“… Risk Ratios (RRs) and corresponding 95% Confidence Intervals (CIs) for the comparison of Evolut PRO and Evolut R devices [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]; ( A ) moderate-to-severe paravalvular leak; ( B ) mild paravalvular leak. Each square represents study point estimate; diamonds reflect the overall effect.…”
Section: Figurementioning
confidence: 99%
“…Recently, the Valve Academic Research Consortium (VARC)-3 proposed an updated endpoint definition of aortic valve clinical research including bioprosthetic valve dysfunction (BVD) and bioprosthetic valve failure (BVF) 7 . In the previous data, supra-annular prostheses demonstrated an excellent haemodynamic performance as compared to intra-annular prostheses in surgical and transcatheter aortic valve replacement 8,9 . Moreover, the data from the UK-TAVI registry demonstrated that TAVI with predilatation was associated with a decrease in valve dysfunction, although it was not confirmed after multiple tests in the short-term follow-up data 10 .…”
Section: Introductionmentioning
confidence: 86%